Converting normal computer screen into 3D displays using parallax barrier - Ang, Robin Wee Kiat (2013)
3D viewing is a recent growing trend. Most technology in 3D viewing requires viewer to wear a 3D glasses or headgear, however, Autostereoscopy is a method whereby 3D images can be viewed without the need for 3D glasses or headgear by employing the illusion of depth. The gaming console, Nintendo 3DS is an example of the usage of Autostereoscopy whereby parallax barrier is used in the device to provide 3D viewing.